2022
DOI: 10.4081/ija.2021.1911
|View full text |Cite
|
Sign up to set email alerts
|

Variation in quality traits of newly developed Serbian wheat cultivars under different environmental conditions of Pannonian plain

Abstract: Introduction of new high-yielding wheat cultivars and intensification of high year-to-year variability require an additional update of information about environmental effects on main wheat quality parameters that is lacking for newly released cultivars in Serbia. The aim of this study was to determine the effect of growing seasons on the technological properties of new Serbian wheat cultivars, and to examine the relationships among the quality traits in different growing seasons. The experiment was set up in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…From statistical analyses utilizing this large dataset, the authors reported a much greater effect of environment on dough extensibility compared to genotype (Eagles et al, 2002). More recently, Živančev et al (2022) reported a significant effect ( p < .01) of environmental conditions due to crop year on dough extensibility for 18 wheat cultivars grown in Serbia over 3 years.…”
Section: Resultsmentioning
confidence: 99%
“…From statistical analyses utilizing this large dataset, the authors reported a much greater effect of environment on dough extensibility compared to genotype (Eagles et al, 2002). More recently, Živančev et al (2022) reported a significant effect ( p < .01) of environmental conditions due to crop year on dough extensibility for 18 wheat cultivars grown in Serbia over 3 years.…”
Section: Resultsmentioning
confidence: 99%
“…Crude protein and oil content were determined by handheld GrainSense NIR Analyzer (Oulu, Finland) and expressed as a percentage of dry matter. According to the study of Živančev et al [42], the correlation between the standard Kjeldahl digestion method for protein determination and the handheld GrainSense NIR Analyzer was positive (r = 0.951). This device is the first of its kind in the world since it weighs only 820 g without batteries.…”
Section: Crude Protein and Oil Content Assessmentsmentioning
confidence: 99%